2020
DOI: 10.1177/1747493020929948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emergent carotid stenting during endovascular therapy for acute anterior circulation stroke patients with tandem occlusion: A multicenter, randomized, clinical trial (TITAN) protocol

Abstract: Background and hypothesis There is no consensus on the optimal endovascular management of the extracranial internal carotid artery steno-occlusive lesion in patients with acute ischemic stroke due to tandem occlusion. We hypothesized that intracranial mechanical thrombectomy plus emergent internal carotid artery stenting (and at least one antiplatelet therapy) is superior to intracranial mechanical thrombectomy alone in patients with acute tandem occlusion. Study design TITAN is an investigator-initiated, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 11 publications
2
32
0
2
Order By: Relevance
“…In accordance with other authors, 23,28 a more conservative approach may be considered for dissection in case of good collaterals, especially considering the potential of healing of the dissected ECL over time. While the ongoing TITAN randomized trial 14 and the EASI-TOC 15 will substantially contribute to the knowledge gained by evaluation of the effect of emergency stenting in TOs, further studies are needed to confirm our results.…”
Section: Emergency Stentingmentioning
confidence: 79%
See 1 more Smart Citation
“…In accordance with other authors, 23,28 a more conservative approach may be considered for dissection in case of good collaterals, especially considering the potential of healing of the dissected ECL over time. While the ongoing TITAN randomized trial 14 and the EASI-TOC 15 will substantially contribute to the knowledge gained by evaluation of the effect of emergency stenting in TOs, further studies are needed to confirm our results.…”
Section: Emergency Stentingmentioning
confidence: 79%
“…5 The Endovascular Acute Stroke Intervention (EASI) trial demonstrated that randomization of patients with TOs is possible, 11 but to date robust data and recommendations about optimal ECL management are lacking. This limited amount of information is reflected in the most recent American 12 and European 13 guidelines, with data from randomized trials on TOs like TITAN (NCT03978988) 14 and the EASI-Tandem Occlusion (EASI-TOC) study, which are still ongoing. 15 The aim of this multicenter study was to explore the impact of the nature of cervical carotid artery lesions, namely CD versus CA, on endovascular management and outcome in patients with AIS and TOs.…”
mentioning
confidence: 99%
“…57 Based on this information a randomized trial by the TITAN collaboration is underway. 58 Based on these preliminary data, we recommend to perform EVT in tandem occlusions with intracranial LVO.…”
Section: Borderline Indications For Evtmentioning
confidence: 95%
“…[ 23 ] The ongoing thrombectomy in tandem occlusion trial is investigating EVT alone compared to EVT with concomitant extracranial carotid stenting. [ 24 ] Application of this dual procedure theoretically increases the success of EVT; however, thrombectomy with contact aspiration demonstrates comparable revascularization rates and shorter operation times than stenting. [ 25 ] A unique EVT technique employs simultaneous intermediate aspiration and stenting.…”
Section: Current Horizons Of Endovascular Mechanical Thrombectomymentioning
confidence: 99%